Kindness according to the prophetic method (Journal of the College of Basic Education, 2026)
The kindness is one of the Islamic law, and a manner of the prophet Mohammed (God's blessing and peace be upon him) in dealing with all of life affair. The Prophet who says: Anything we do it with kindness is good and nice, and anything we do it without kindness is bad. We found a kindness is to adorn every act by the prophet (peace be upon him) with the family, relatives, women, children, adult, and young even with enemies or with animals. This good manner of the prophet founded it even with severity situations such as Halal slaughter of sacrifices which it is to approach to the God, so, there is a specific rules in a slaughter to prevent harming animals; which is a torturing of animals is considered a great sin. At last, if we need to mention every situation of the prophet (peace be upon him) that adorned with kindness, the ink and papers of the world will not sufficient of that; and it is not credible that is such this religion is accused by terror and barbarian and it's prophet who described and urged deal with kindness and mercy in all of life fields.